Sudden death of entanglement and teleportation fidelity loss via the Unruh effect - Landulfo, André G.S. [UNESP]; Matsas, George E.A. [UNESP] (American Physical Society (APS), 2009)
We use the Unruh effect to investigate how the teleportation of quantum states is affected when one of the entangled qubits used in the process is under the influence of some external force. In order to reach a comprehensive understanding, a detailed analysis of the acceleration effect on such entangled qubit system is performed. In particular, we calculate the mutual information and concurrence between the two qubits and show that the latter has a sudden death at a finite acceleration, whose value will depend on the time interval along which the detector is accelerated. © 2009 The American Physical Society.